An industrial geography of cocaine - Allen, Christian Michael (Latin American studies : social sciences and law, 2005)
Through the lens of economic geography: cocaine in space and place -- Globalization and the competitive strategies of criminal enterprises -- From coca to cocaine -- Colombian competitive advantage in cocaine -- Cocaine distribution and Mexico's growing competitive advantage -- Marketing cocaine in the United States -- Policy implications -- Conclusions: Through a glass, darkly